Penanaman Toleransi pada Anak Usia Dini (Studi Umat Muslim dan Hindu di Kediri Jawa Timur) - Asy'ari, Asy'ari; Sensia, Mayank Putri; Mukti, Ali (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
Education is important because education can change and also shape a person's personal character. To create a person's character, cultivation is needed from an early age. This article discusses instilling tolerance values ​​in early childhood. There is also the aim of this article, to show the urgency of instilling the value of tolerance from an early age. There are also results from this paper, first, to instill the value of tolerance, influenced by environmental factors and the conditions in which children live; secondly, the importance of awareness and tolerance values ​​must be applied from an early age because character and personality will influence one's social life. There are also values ​​that are instilled from an early age, including; Awareness values ​​must start from honesty, mutual respect, helping each other regardless of social status, the color of their clothes.